Nitrite Reductase Mutants as an Approach to Understanding Nitrate Assimilation in Chlamydomonas reinhardtii - Navarro, María Teresa (American Society of Plant Physiologists, 2000)
We constructed mutant strains lacking the nitrite reductase (NR) gene in Chlamydomonas reinhardtii. Two types of NR mutants were obtained, which either have or lack the high-affinity nitrate transporter (Nrt2;1, Nrt2;2, and Nar2) genes. None of these mutants overexpressed nitrate assimilation gene transcripts nor NR activity in nitrogen-free medium, in contrast to NR mutants. This finding confirms the previous role proposed for NR on its own regulation (autoregulation) and on the other genes for nitrate assimilation in C. reinhardtii. In addition, the NR mutants were used to study nitrate transporters from nitrite excretion. At high CO(2), only strains carrying the above high-affinity nitrate transporter genes excreted stoichiometric amounts of nitrite from 100 μm nitrate in the medium. A double mutant, deficient in both the high-affinity nitrate transporter genes and NR, excreted nitrite at high CO(2) only when nitrate was present at mm concentrations. This suggests that there exists a low-affinity nitrate transporter that might correspond to the nitrate/nitrite transport system III. Moreover, under low CO(2) conditions, the double mutant excreted nitrite from nitrate at micromolar concentrations by a transporter with the properties of the nitrate/nitrite transport system IV.